The Effect of Motivation and Transactional Leadership Style on Employee Job Satisfaction at Cable Company in Indonesia - Anastasia Cindy Jayadi; Sanny Ekawati (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to determine the relationship between motivation and transactional leadership style on employee job satisfaction at a cable company in Indonesia. Ali et al. [1] and Amin et al. [2] found that transactional leadership style had insignificant effect to job satisfaction. Moreover, a study conducted by Anghelache [3] discovered that there is insignificant effect between motivation and job satisfaction. In this study, the sample size was 75 respondents who worked for a cable company in Indonesia. This study’s sampling method was purposive sampling by distributing online questionnaires in google forms. This study used SEM-PLS with Smart PLS software version 3.0.in processing the data. The findings indicated that motivation and transactional leadership styles have a positive and significant effect on employee job satisfaction at one of cable companies in Indonesia.